2015
DOI: 10.2495/sdp-v10-n5-685-700
|View full text |Cite
|
Sign up to set email alerts
|

Environmental practice and its effect on the sustainable development of eco-industrial parks in China

Abstract: After more than a decade of development, eco-industrial parks (EIPs) have made significant progress in saving resources and protecting the environment in China. Meanwhile, many problems have emerged, such as poor stability, poor profitability and weak eco-industrial chains, which have impeded the EIP's sustainable development. Faced with variable environmental practices and limited resources and capital, EIPs need to address suitable environmental practices seriously to configure resources reasonably and ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…e.g., Dolný and Harabiš 2012 ; Tear et al 2014 ; Nungesser et al 2015 ; Alberdi et al 2016 ), as well as organizations, groups and professions engaged in the process (cf. e.g., Hosseini and Rezaei 2013 ; de Nooy 2013 ; Qu et al 2014 ; Henckens et al 2016 ; Romañach et al 2016 ), it is very difficult to develop one application or access point which would satisfy needs and expectations of all applicable groups of users, taking into account functionality, available datasets or conditions of data use. Taking network services required for operation and maintenance of the SDI into account, the map viewer functionalities presented in this study (Table 1 ) and suggestions of spatial planners concerning data formats allow for a type of universal solution to be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…e.g., Dolný and Harabiš 2012 ; Tear et al 2014 ; Nungesser et al 2015 ; Alberdi et al 2016 ), as well as organizations, groups and professions engaged in the process (cf. e.g., Hosseini and Rezaei 2013 ; de Nooy 2013 ; Qu et al 2014 ; Henckens et al 2016 ; Romañach et al 2016 ), it is very difficult to develop one application or access point which would satisfy needs and expectations of all applicable groups of users, taking into account functionality, available datasets or conditions of data use. Taking network services required for operation and maintenance of the SDI into account, the map viewer functionalities presented in this study (Table 1 ) and suggestions of spatial planners concerning data formats allow for a type of universal solution to be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concept of SD is very old and that is emerged in 1972. It has more than 100 different definitions and interaction with numerous indicators and socio-economic activities in a country [5]. Hence, it is projected that SD cannot be achieved without environmental development [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, extensive deforestation created a complication to maintain SD especially in developing economies. SD pursues to satisfy the demands of current generations without decline the ability of next generations to achieve their own necessities [4][5][6]. In above perspectives, theoretical review has shown that SD is an integration of economic, human, social, technological and environmental development [3,4,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations